Research Progress of Polysaccharide-Gold Nanocomplexes in Drug Delivery - Ming Song; Adila Aipire; Elzira Dilxat; Jianmin Li; Guoyu Xia; Ziwen Jiang; Zhongxiong Fan; Jinyao Li (Pharmaceutics, 2024)
Clinical drug administration aims to deliver drugs efficiently and safely to target tissues, organs, and cells, with the objective of enabling their therapeutic effects. Currently, the main approach to enhance a drug’s effectiveness is ensuring its efficient delivery to the intended site. Due to the fact that there are still various drawbacks of traditional drug delivery methods, such as high toxicity and side effects, insufficient drug specificity, poor targeting, and poor pharmacokinetic performance, nanocarriers have emerged as a promising alternative. Nanocarriers possess significant advantages in drug delivery due to their size tunability and surface modifiability. Moreover, nano-drug delivery systems have demonstrated strong potential in terms of prolonging drug circulation time, improving bioavailability, increasing drug retention at the tumor site, decreasing drug resistance, as well as reducing the undesirable side effects of anticancer drugs. Numerous studies have focused on utilizing polysaccharides as nanodelivery carriers, developing delivery systems based on polysaccharides, or exploiting polysaccharides as tumor-targeting ligands to enhance the precision of nanoparticle delivery. These types of investigations have become commonplace in the academic literature. This review aims to elucidate the preparation methods and principles of polysaccharide gold nanocarriers. It also provides an overview of the factors that affect the loading of polysaccharide gold nanocarriers with different kinds of drugs. Additionally, it outlines the strategies employed by polysaccharide gold nanocarriers to improve the delivery efficiency of various drugs. The objective is to provide a reference for further development of research on polysaccharide gold nanodelivery systems.